Emerging fluconazole-resistant Candida parapsilosis in Australia: a case cluster and insights into the genetic diversity of this species - Perera, Manoshi; Fong, Winkie; Haywood, Rose; Sullivan, Geraldine J.; Wang, Qinning; Halliday, Catriona L.; Dowsett-Moeahu, Sharn; Biswas, Chayanika; Firacative, Carolina; Liu, Marie-Claire; Weeks, Kerry; Hardiman, Robyn; et al. (Frontiers in Microbiology, 2026)
BackgroundNosocomial outbreaks of fluconazole-resistant Candida parapsilosis are concerning. Here we characterised a cluster of fluconazole-resistant C. parapsilosis utilising whole-genome sequencing (WGS) and correlate phenotypic azole resistance with resistome-based WGS analysis of azole resistance-conferring mutations.Materials and methodsSeventeen C. parapsilosis isolates were studied. Group 1: seven fluconazole-resistant isolates from a hospital intensive care unit (ICU) outbreak (2023–2024), Group 2: six isolates from a historical case cluster, Group 3: four additional unrelated isolates. Minimum inhibitory concentrations (MICs) were determined using SENSITITRE AUSNMRC1 (TREK Diagnostics). Single nucleotide polymorphism (SNP)-based phylogenomic analysis was undertaken using two (MycoSNP and custom-based) bioinformatic pipelines to assess relatedness. Target-gene mutations for azole resistance were evaluated.ResultsICU patient risks for fluconazole-resistant C. parapsilosis included presence of intravascular device and recent broad-spectrum antimicrobial use. Core SNP-based analysis showed clustering of Group 1, and separately, of Group 2 isolates. With greater genetic similarity (range <2–9 SNP difference) between isolates within Group 1, than between these and Group 2 and 3 isolates (1700–3,000 SNPs); the in-house pipeline yielded the same phylogenetic pattern with isolates within both Group 1 and 2 clusters separated by ≅100 SNPs (range 47–124). The eight fluconazole-resistant (MIC >64 mg/L) isolates had ERG11 Y132F and TAC1 D444Y mutations which were absent in fluconazole-susceptible isolates. The mutation ERG11 R398I was present in azole-resistant and azole-susceptible strains.ConclusionGenomic relatedness amongst clustered isolates was confirmed in this first fluconazole-resistant C. parapsilosis outbreak in Australia. Fluconazole-resistant isolates harboured ERG11 Y132F and TAC1 D444Y mutations. The protracted outbreak underscores the need to prioritise enhanced surveillance.